KETERSEDIAAN SARANA PRASARANA PENDIDIKAN DALAM UPAYA MENINGKATKAN PELAYANAN BELAJAR DI SMASWASTA WISUDA PONTIANAK - Romiansyah Romiansyah; Sulistyarini Sulistyarini; Bambang Genjik (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
Abstract This study aims to identify the availability of educational facilities that used, what are the standards of educational infrastructure and obstacles in creating comfort in study services at SMAS Wisuda. The teachniques of this reasech are observation, interview, documentary, with tools of data collection in form of questionnaires and documentation. The data sources of this study were a headmaster and students. Based on the data it showed that: (1) the availability of educational infrastructure provided by SMAS Wisuda Pontianak is still insufficient with 3 local classrooms. Which has a library, a computer laboratory, a leadership room, a teacher room, an administration room, a counseling room, an UKS room, a student organization room, a latrine/toilet, a building, and a playground/an exercise room, which there are still some incomplete infrastructure suggestions. (1) based on the results of the research, the use of each educational market provided by the school based on the available facilities, there are several infrastructures that suitable for using and some which are not yet suitable for applying. (2) the constraint in creating comfort in learning services at Graduation High School is that the infrastructure is still limited so it is difficult to convey important materials to students. Keywords: education infrastruture and learning services.